Reconstruction of past atmospheric CH4 concentration from the firn air data at Dome Fuji (scientific note) - Sugawara, Satoshi; Kawamura, Kenji; Aoki, Shuji; Nakazawa, Takakiyo; Hashida, Gen (2003)
P(論文) Air samples were collected from different depths of the firn layer at Dome Fuji in December 1998 and analyzed for CH4 concentrations. The age distribution of CH4 in the firn was calculated by using a one-dimensional numerical model, and then the inverse method was applied to reconstruct variations of atmospheric CH4 in the past. The age distribution function was calculated by including processes of molecular diffusion, downward air advection and bubble trapping in the snow-ice transition zone. Once the age distribution function is calculated, the vertical distribution of CH4 in the firn layer can be reconstructed by a linear combination of the age distribution functions weighted by the atmospheric CH4 concentrations in the past. Therefore, the most plausible past atmospheric record of CH4 can be derived iteratively so that its observed profile in the firn layer was reproduced well. In order to check the calculation scheme, the estimated variation of atmospheric CH4 was compared with direct measurements in the Antarctic region. They were in good agreement with each other, even for rapid slowing down of the secular increase observed in the 1990's. departmental bulletin paper